4 Evaluation of a creative photography workshop for children and young people following a diagnosis of PIMS-TS. (15th December 2021) - Freeman, Anita; Hatton, Philippa; Grant, Karlie; Mcmonnies, Kate; Moshal, Karyn; Penner, Justin; Sweet, Rebecca; Ovin, Felicia; Bird, Annie; Berger, Zoe
Abstract : Background: Paediatric Multisystem Inflammatory Syndrome Temporally Associated with SARS-CoV-2 (PIMS-Ts) is a rare inflammatory condition affecting children and young people (CYP). Many CYP report behavioural/mood changes, concentration difficulties and increased isolation, which for some occurred following an admission to intensive care. This workshop aimed to reduce CYPs' experiences of isolation using a strength-based Narrative Therapy group approach. Methods: The workshop was co-facilitated by a photography artist, psychologists and ID clinical team in local gallery to create a safe, therapeutic space. The workshop involved activities to allow CYP to explore their identity through the use of photography, and to enable them to share their stories of their PIMS-TS experiences with their peers. The participants completed pre and post outcome evaluation measures and a free text feedback form. Two weeks following the workshop, parents/carers and CYP were contacted to participate in a semi structured interview to evaluate the impact of the workshop on CYP relationship to their health condition and hospital experience. Results: The workshop was attended by 9 CYP (aged 8–11 years). Participants indicated that the workshop had led to increased comfort and confidence in talking about their health condition and that they had appreciated the opportunity to meet other CYP. Discussion: Feedback suggests that an arts-based workshop was an effective peer support-based psychological intervention. Conclusion: These findings suggest that there are psychological benefits to narrative therapy-based arts group for CYP post discharge, to share and reflect on their health and hospital experiences with those who have lived through similar experiences. Given that treatment protocols are still being refined for PIMS-TS, the findings of this project suggest that CYP and families may benefit from follow-up interventions to better understand and identify their psychological needs post diagnosis.